(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Sociolinguistic the study of language the relationship between language and society.It means that Socio means social or related to society and Linguistics means the science of language. They are concerned with identifying the social purposes of language and the means through which it is utilized to express social meaning. They are interested in understanding why we speak differently in various social circumstances. A great deal of knowledge about language functioning, social interactions in a society, and how people express and build parts of their social identity through their language may be learned by observing how people use language in various social circumstances